Ma’agan Michael ship - Martins, Adolfo Miguel (iMARECULTURE H2020 Project: Advanced VR, iMmersive serious games and Augmented REality as tools to raise awareness and access to European underwater CULTURal heritagE, 2018)
Abstract: This detailed 3D model of the Ma’agan Michael ship was inspired on what we know from the archaeological record. There are two scholarly reconstructions of this hull. We based our model on the Jay Rosloff set of lines mainly for aesthetic reasons. Even though Henry Winters and Yaacov Kahanov produced a second set of lines, later and with more data, we decided to develop our model from Jay Rosloff’s drawings because they look more in tune with the iconography available for vessels of this period. There are several versions available in different formats.
Keywords: 3D model; Maggan Mikhael; iMARECULTURE; 3D library